Distinctive adaptive response to repeated exposure to hydrogen peroxide associated with upregulation of DNA repair genes and cell cycle arrest (2016)
Many environmental and physiological stresses are chronic. Thus, cells are constantly exposed to diverse types of genotoxic insults that challenge genome stability, including those that induce oxidative DNA damage. However, most in vitro studies that model cellular response to oxidative stressors employ short exposures and/or acute stress models. In this study, we tested the hypothesis that chronic and repeated exposure to a micromolar concentration of hydrogen peroxide (H2O2) could activate DNA damage responses, resulting in cellular adaptations. For this purpose, we developed an in vitro model in which we incubated mouse myoblast cells with a steady concentration of ~50 ?M H2O2 for one hour daily for seven days, followed by a final challenge of a 10 or 20X higher dose of H2O2 (0.5 or 1 mM). We report that intermittent long-term exposure to this oxidative stimulus nearly eliminated cell toxicity and significantly decreased genotoxicity (in particular, a >5-fold decreased in double-strand breaks) resulting from subsequent acute exposure to oxidative stress. This protection was associated with cell cycle arrest in G2/M and induction of expression of nine DNA repair genes. Together, this evidence supports an adaptive response to chronic, low-level oxidative stress that results in genomic protection and up-regulated maintenance of cellular homeostasis.